Spectrum of Different Heart Disease among Children Under 5 Years of Age - Hamail Amin, Riffat Naeem, Farah Rafique, Farhat Ijaz, Ahmad Tariq, Awais Ahmad, Rana Khurram Aftab, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: It is a well-known finding that cardiac diseases in the pediatric population contribute majorly to morbidity and mortality around the globe and is supported by extensive clinical research. A generalized burden of the disease in Pakistan is as high as above 40,000 congenital cardiac defects being reported among newborn babies. It has been documented those congenital cardiac disorders are among the top three causes of neonatal mortality around the world. This study is focused on studying different types of cardiac problems acknowledged among children who are younger than five years and studying the prevalence and burden of disease and assessing the frequency with which they occur in the Pakistani population. Methodology: The conducted study was cross sectional with descriptive approach. The time duration of the study was of ten months which started in February 2021 and concluded in November 2021. The study was carried out at pediatrics department of Ittefaq Hospital and Jinnah Hospital, Lahore Pakistan, after taking ethical approval from the respective departments. The sample size of the study was expected to be around 200 participants. All the recruited participants must meet the age limitations who were under 5 years old. The incidence of heart disease was assumed to be 5%. The recruited participants must show signs and symptoms which suggest the incidence of cardiac problems. Participants with pre-existing heart diseases were eliminated from the study. The participants underwent clinical and lab testing before start of the study Result: The prevalence of 89% (n= 178) of participants was diagnosed with congenital heart disease whereas 11% (n= 22) of participants were detected to have acquired heart diseases. Among diagnosed participants with congenital heart disease, females were found to be 1.2 times more likely to be affected. Among the patients diagnosed with congenital heart diseases, the most common finding was that of ventricular septal defect with a prevalence of 29.5% followed by an atrial septal defect with a prevalence of 26% and in acquired heart disease myocarditis accounted for 91% of the diagnosis. Conclusion: The present study concluded that the prevalence of cardiac condition among children under 5 years is highly prevalent. Among cardiac condition of pediatric patient congenital heart diseases remain highly incidental with ventricular septal defect being the most common congenital condition. Among acquired cardiac condition, myocarditis was the most frequent finding.